2022
DOI: 10.2478/rjti-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Life E-VIA: Prototypal Low-Noise Road Surface for the Reduction of Electric Vehicle Rolling Noise in Urban Area

Abstract: In both the current and foreseen context of significant development of the electric vehicle (EV) fleet, a future increasing ratio of EVs in the urban traffic is expected, still enhanced in low-emission zones involving bans or restricted access to other vehicles. EVs are known to be quieter than conventional vehicles at low speed because of a low motor noise emission, resulting in a higher prevalence of rolling noise in the environmental noise. EVs differ from conventional vehicles in several parameters that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Studies have shown that this effect increases further with acceleration, i.e. with tyre torque [3]. Even though also characterized by the occurrence of torque, for normal braking and recuperation, in contrast, only small changes have been observed [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that this effect increases further with acceleration, i.e. with tyre torque [3]. Even though also characterized by the occurrence of torque, for normal braking and recuperation, in contrast, only small changes have been observed [4].…”
Section: Introductionmentioning
confidence: 99%